2020
DOI: 10.1002/ehf2.12793
|View full text |Cite
|
Sign up to set email alerts
|

Gateway and journey of patients with cardiac amyloidosis

Abstract: Aims Advances have been made over the last decade in the management of cardiac amyloidosis (CA), but a delayed diagnosis is still common. The aim of this study was to describe the journey to CA diagnosis from initial clinical and to analyse time to diagnosis. Methods and results Between January 2001 and May 2019, 270 consecutive patients with CA diagnosed at Toulouse University Hospital were retrospectively included in this cross-sectional study: 111 (41%) light chain amyloidosis, 122 (45%) wild-type transthyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
(80 reference statements)
6
17
0
Order By: Relevance
“…The most common type of amyloidosis seen in our participants practice was AL which is indeed a rare disease. The majority of our participants stated the mean delay from the first presentation with cardiac symptoms to diagnosis was no longer than 24 months, which is significantly lower than it was previously described in a large study involving patients from the UK National Amyloidosis Centre where a median diagnostic delay of 39 months was reported [15], but consistent with the results from another study involving patients with CA diagnosed at Toulouse University Hospital which reported a median delay between symptom onset and diagnosis of 8, 10 and 18 months in AL, ATTRwt and ATTRv, respectively [16]. Only proper training of healthcare personnel can improve the diagnostic delay in this condition as early diagnosis combined with timely initiation of the disease modifying treatment may lead to disease stabilization and a significant improvement in patient status [27].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most common type of amyloidosis seen in our participants practice was AL which is indeed a rare disease. The majority of our participants stated the mean delay from the first presentation with cardiac symptoms to diagnosis was no longer than 24 months, which is significantly lower than it was previously described in a large study involving patients from the UK National Amyloidosis Centre where a median diagnostic delay of 39 months was reported [15], but consistent with the results from another study involving patients with CA diagnosed at Toulouse University Hospital which reported a median delay between symptom onset and diagnosis of 8, 10 and 18 months in AL, ATTRwt and ATTRv, respectively [16]. Only proper training of healthcare personnel can improve the diagnostic delay in this condition as early diagnosis combined with timely initiation of the disease modifying treatment may lead to disease stabilization and a significant improvement in patient status [27].…”
Section: Discussionsupporting
confidence: 87%
“…In a study involving 1034 patients with CA from the UK National Amyloidosis Centre with a subset of 534 patients in whom complete data on hospital service usage were available, there was a median diagnostic delay from the first presentation with cardiac symptoms of 39 (8-78) months in patients with ATTRwt, with 42% waiting more than 4 years for the diagnosis to be established and a median delay of 25 (4-60) months in the ATTRv group [15]. Another retrospective study involving 270 consecutive patients with CA diagnosed at Toulouse University Hospital reported a median delay between symptoms onset and diagnosis of 8 (5-14), 10 (3-34) and 18 (4-49) months in AL, ATTRwt and ATTRv, respectively, where patients encountered a median number of 2 (1-7) phisicians and performed a median number of 3 (1)(2)(3)(4)(5)(6)(7)(8) tests before the diagnosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of our participants stated the mean delay from the first presentation with cardiac symptoms to diagnosis was no longer than 24 months, which is significantly lower than it was previously described in a large study involving patients from the UK National Amyloidosis Centre where a median diagnostic delay of 39 months was reported [ 15 ], but consistent with the results from another study involving patients with CA diagnosed at Toulouse University Hospital which reported a median delay between symptom onset and diagnosis of 8, 10 and 18 months in AL, ATTRwt and ATTRv, respectively [ 16 ]. Only proper training of healthcare personnel can improve the diagnostic delay in this condition as early diagnosis combined with timely initiation of the disease modifying treatment may lead to disease stabilization and a significant improvement in patient status [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…In a study involving 1034 patients with CA from the UK National Amyloidosis Centre with a subset of 534 patients in whom complete data on hospital service usage were available, there was a median diagnostic delay from the first presentation with cardiac symptoms of 39 (8–78) months in patients with ATTRwt, with 42% waiting more than 4 years for the diagnosis to be established and a median delay of 25 (4–60) months in the ATTRv group [ 15 ]. Another retrospective study involving 270 consecutive patients with CA diagnosed at Toulouse University Hospital reported a median delay between symptoms onset and diagnosis of 8 (5–14), 10 (3–34) and 18 (4–49) months in AL, ATTRwt and ATTRv, respectively, where patients encountered a median number of 2 (1–7) physicians and performed a median number of 3 (1–8) tests before the diagnosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the latest expert consensus on CA diagnosis presents this restrictive pattern or a grade ≥II LVDF as important criteria to suggest the presence of CA, despite recent extensive and multimodal CA characterisation [ 6 , 15 ]. However, cardiologists should consider CA prior to this stage to avoid delayed diagnosis, still common despite better disease knowledge by the cardiologists [ 16 ]. Applying the ASE-EACVI recommendations, we found that up to 25% of the study population had grade I LVDF with likely normal LV filling pressures [ 17 ].…”
Section: Discussionmentioning
confidence: 99%